2015
DOI: 10.4049/jimmunol.1402771
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated and Disease-Associated Autoantibody Repertoires in Healthy Colostrum and Maternal and Newborn Cord Sera

Abstract: In this work, we studied autoantibody repertoires and Ig isotypes in 71 mothers and their 104 healthy newborns (including twins and triplets delivered term or premature). Newborns receive maternal IgG Abs via the placenta before birth, but developing infants must produce their own IgM and IgA Abs. We used an Ag microarray analysis to detect binding to a selection of 295 self-Ags, compared with 27 standard foreign Ags. The magnitude of binding to specific self-Ags was found to be not less than that to the forei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 114 publications
(64 reference statements)
1
19
0
2
Order By: Relevance
“…There are reports of pre-symptomatic patients displaying serum autoantibodies up to 20 years prior onset of an autoimmune disease, for example, anti-TRIM21 reactivity related to Sj€ ogren syndrome [17] and anti-citrullinated-peptide antibodies (ACPA) related to rheumatoid arthritis [18]. Several studies have shown that healthy individuals have detectable levels of serum autoantibodies which suggests that autoantibody positivity is not necessarily disease associated [19][20][21][22][23][24][25][26][27][28][29]. It remains to be seen if any of the individuals we have investigated herein develop autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of pre-symptomatic patients displaying serum autoantibodies up to 20 years prior onset of an autoimmune disease, for example, anti-TRIM21 reactivity related to Sj€ ogren syndrome [17] and anti-citrullinated-peptide antibodies (ACPA) related to rheumatoid arthritis [18]. Several studies have shown that healthy individuals have detectable levels of serum autoantibodies which suggests that autoantibody positivity is not necessarily disease associated [19][20][21][22][23][24][25][26][27][28][29]. It remains to be seen if any of the individuals we have investigated herein develop autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The IgG content in breast milk is similar during the first week after birth and later in the lactating period. Only a small proportion of the milk antibodies are absorbed from the gut and into the baby's circulation . Being breastfed reduces the risk for many autoimmune diseases , especially desirable for children of MG mothers who have already a genetic predisposition.…”
Section: Breastfeedingmentioning
confidence: 99%
“…The initial study of maternal-cord autoantibodies was expanded recently to a study of 71 mothers and their 104 newborns (including twins and triplets); we also studied antibody reactivities detectible in maternal colostrum [22]. The findings reported in the initial, small study were confirmed in this much larger set of subjects.…”
Section: The Immunological Homunculus At Birthmentioning
confidence: 84%